Phase and Micro-Structural Characterization of Sanitary- Ware Fired at Different Temperature - Hassan, Ather; Iqbal, Yaseen; Ilyas, Syed Zafar (Mehran University Research Journal of Engineering and Technology, 2017)
The three main ingredients of sanitary-ware are clay, feldspar and quartz. This ware is being widely used and has therefore, attracted the attention of researchers from time to time. Consequently, it has been extensively investigated. The present study describes the phase and micro-structural analysis of sanitaryware samples collected from local (Durr Ceramics Peshawar) industry. XRD (X-Ray Diffraction) of samples fired at 1100oC reveals the presence of Î±-quartz and primary mullite only. In addition to a-quartz and primary mullite, elongated needles of secondary mullite were also present in samples fired at 1200 and 1300oC. Unlike typical vitreous ceramics bodies, regions containing elongated secondary mullite originating from the clay relict and growing into the feldspar relict were few in number which is consistent with the high clay content in the starting body ingredients of the investigated samples. Another sample investigated for comparison purposes, contained all the phases mentioned above along with some corundum grains which indicated that the composition of sanitary ware varied from manufacturer to manufacturer. EDS (Energy Dispersive Spectroscopy) detected high concentration of Fe in some regions in the bulk but the glaze did not contain any Fe.